Hunchback-independent silencing of late Ubx enhancers by a Polycomb Group Response Element. - Poux, S (1996)
Drosophila homeotic genes are kept silent outside of their appropriate expression domains by a repressive chromatin complex formed by the Polycomb Group proteins. In the case of the Ubx gene, it has been proposed that the early repressor HB, binding at enhancers, recruits the Polycomb complex and specifies the domain of repression. We show that some Ubx enhancers are activated after blastoderm. If a Polycomb Response Element (PRE) is combined with such late enhancers, repression of a reporter gene can be established everywhere in the embryo, irrespective of the presence or absence of hunchback protein. If, however, these late enhancers are combined with a Ubx early enhancer, as well as a PRE, repression is established only where the reporter gene was inactive at early stages. These results imply that the Polycomb complex is not dependent on hunchback and suggest that the pattern of silencing reflects rather the state of activity of the gene at the time the Polycomb complex is formed.